Main psychological impacts on children victims of sexual abuse (Research, Society and Development, 2021)
This article sought to verify the effects of sexual abuse on children and the psychological impacts left in the short and long term. Thus, a discussion was held about the contributions of monitoring and the psychologist's intervention in handling abused children. The methodological procedure included systematic bibliographic research on reference materials in the area, including books, articles and legislative references. Therefore, the articles were correlated and an overview of the topic in question in the pandemic scenario was built.